Efektivitas Komposisi Media Tanam Arang Sekam dan Cocopeat terhadap Pertumbuhan dan Produktivitas Labu Madu Hibrida - Alfian, Vivin; Zaedan Fitri, Mohammad (Program Studi Agroteknologi, 2022)
Pumpkin honey is a plant that has high economic value. In addition, honey pumpkin contains nutrients such as Provitamin A, Protein, Carbohydrates, Calcium, Phosphorus, Iron, Vitamin B, and, Vitamin C. The thing that must be considered to increase productivity in cultivation is the planting medium. A good planting medium is a planting medium that complies with the principles of GAP (Good Agriculture Practices), which does not contain contaminants of hazardous and toxic materials (B3). Husk charcoal and cocopeat are organic materials that can be used to mix planting media. The purpose of this study was to examine the effectiveness of the composition of rice husk charcoal and cocopeat growing media on the growth and productivity of honey pumpkins. This study used a randomized block design (RAK) with seven treatments and four replications. The treatments studied were control (V0); 1 cup of husk charcoal (V1); 2 cups of husk charcoal (V2); 1 cup cocopeat (V3); 2 cups cocopeat (V4); 1 cup charcoal husk + 1 cup cocopeat (V5); 2 cups of husk charcoal + 2 cocopeat (V6). The results showed that there was an interaction beetwen the growing media on vegetative and generative growth, productivity, and high quality of honey pumpkin plants.